PENGARUH PELATIHAN, KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT XYZ - Sinta Wahyu Salsabilla; Heru Baskoro (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine the effect of training, competence, and motivation on employee performance at PT XYZ. The approach used in this study is descriptive analysis with questionnaire data research instruments. statistical analysis used in this study namely validity test, reliability test, classic assumption test, using multiple linear regression analysis test, hypothesis testing using t test and f test and analysis of the coefficient of determination. The variables used in this study are training (x1), competency (x2), and motivation (x3) which are hypothesized to affect employee performance. the sample in this study amounted to 123 people using saturated and quantitative sampling methods. The results of this study can be concluded that training has the most influence on employee performance and is followed by competence and motivation. So that the leadership of PT XYZ must develop a model of training and motivation for employees to improve the quality of employee performance.